Perancangan Standar Proses Produksi Berdasarkan Indikator Good Manufacturing Practices (GMP) pada Industri Kecil dan Menengah Bidang Pangan - Nofriani Fajrah; Sri Zetli; Muhammad Rasid Ridho; Rifaldi Hakiki; Moses Adrianus Sembiring; Riski Ade Putra (LPPM Universitas Putera Batam, 2025)
Small and Medium Industries (SMI) face challenges in ensuring product safety and quality due to the optimal implementation of Good Manufacturing Practices (GMP). This study aims to design a standard production process framework based on GMP indicators to improve the process quality in snack food SMIs. The research employs a case study approach with a mixed-methods design at a chipproducing SMI in Batam City. The DMAIC (Define, Measure, Analyze, Improve, Control) methodology was applied to analyze historical defect data, observations, and in-depth interviews. Initial measurement results showed a defect rate of 12.3% and a GMP audit score of 58%. The analysis revealed the root causes of the defects, namely the absence of SOPs, machine instability, and an unsupportive layout. The proposed solution is a framework encompassing layout modification, SOP development, training programs, and a daily monitoring checklist form integrated with GMP indicators. The study concludes that the systematic integration of GMP and DMAIC is effective in creating sustainable improvements and provides a practical contribution in the form of an adoptable model for similar food SMIs.